A Review of Western and Traditional Chinese Medical Approaches to Managing Nonalcoholic Fatty Liver Disease. (31st October 2016) - Hsu, Wei-Fan; Sheen, Lee-Yan; Lin, Hung-Jen; Chang, Hen-Hong
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a disease of attention because of increase in prevalence from 20% to 41%. The clinical and pathological conditions in patients with NAFLD range from steatosis alone to nonalcoholic steatohepatitis (NASH) with or without fibrosis to hepatic cancer. In the United States, NAFLD was the second-leading indication for liver transplant between 2004 and 2013. Although imaging studies such as magnetic resonance elastography and the use of diagnostic panels and scoring systems can provide a fairly accurate diagnosis of NAFLD, there are few treatment options for patients with mild to moderate disease other than lifestyle modification. Many of the currently used medical treatments have been shown to cause severe side effects and some have been shown to be associated with increased risk for certain types of cancer. In recent years, a number of traditional Chinese herbal treatments have been examined for their potential uses as treatment for NAFLD. In this review, we provide a general overview of NAFLD and a survey of Western pharmacologic drugs currently used to treat the disease as well as the results of recent studies on the effectiveness of traditional Chinese herbal remedies for managing nonalcoholic fatty liver disease.